Reassessing Indonesia’s Economic Hedging Strategy under Prabowo amid Escalating United States–China Rivalry - Afrizal Fajri; Rifky Apriansyah, Muhammad (Jurnal Hubungan Internasional, 2026)
This article analyzed Indonesia’s two-pronged foreign policy strategy to reduce economic losses, or economic hedging, under the leadership of President Prabowo Subianto, regarding the competition between the United States and China. Unlike previous literature, which emphasizes domestic political factors and normative commitments to the principle of non-alignment as the main reasons for Indonesia’s foreign policy strategy, this article adopted a framework of economic hedging concretely realized through various instruments. Using qualitative methods, this article applied Tessman and Wolfe’s model to assess whether Indonesia’s recent economic diplomacy can be understood as a coherent strategy. This assessment was based on four main principles: capacity building, avoiding open confrontation, centralizing inter-agency coordination, and calculating long-term profits and losses. Empirical findings unveiled that contemporary Indonesian economic diplomacy, including BRICS membership, consolidation of state wealth funds, diversification of foreign investment, and selective market liberalization, clearly followed the logic of Tessman and Wolfe. However, this article also offers a more moderate perspective by emphasizing structural factors, in which economic hedging is understood as a risk management strategy in the face of increased geopolitical contestation, domestic socio-economic pressures, and asymmetric dependencies. This article enriches the literature on the position of middle powers by showcasing that the maneuvering space of non-aligned countries tends to narrow amid an increasingly polarized and divided global political economy.